(1574) Some issues of the European Unification and their monetary impacts on the Egyptian Pound- (An Overview) بعض قضايا التوحيد الأوروبي وتأثيراتها النقدية على الجنيه المصري - (نظرة عامة) - Abd Elsalam, Fadia (The Institute of National Planning, 2018)
The European community has made enormous progress on the road to European economic and monetary union during the last few years. One recalls the community's efforts in the so-called Werner Plan at the end of the sixties. A second attempt in 1988 (*), took a different course. Two years later on July 1, 1990, stage one of the European economic and monetary union began. The institutional - stage would begin with the establishment of a European system’of Central Bank (Eurofed). In October 1990, the heads of state and